PENDAMPINGAN LEMBAGA DAKWAH MAJELIS WAKIL CABANG NAHDLATUL ULAMA’ KECAMATAN BOYOLANGU DALAM MEMBUMIKAN KONSEP MODERASI BERAGAMA BAGI PENGURUS NU SE-KECAMATAN BOYOLANGU - Siswanto, Eko; Mubarok, Sofarul (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
Boyolangu District is characterized by high religious and cultural diversity, which creates potential social tensions when the concept of religious moderation is not well understood. Nahdlatul Ulama (NU), as the largest Islamic organization in Indonesia, holds a strategic role in promoting inclusive religious practices at the grassroots level. This study aims to describe the level of understanding and implementation of religious moderation among NU Branch (Ranting) administrators in Boyolangu District, analyze the strategies employed by the Dakwah Council of MWC NU Boyolangu in providing guidance, and evaluate the effectiveness of these approaches. The methods used include interactive training, continuous field mentoring, interfaith dialogue facilitation, and the use of digital media for disseminating moderate religious messages. Both quantitative and qualitative evaluations were conducted to assess changes in understanding and practice. The findings reveal that the administrators’ understanding of the concept of religious moderation remains limited, as observed during the mentoring session conducted on October 4, 2025. The strategies adopted by the Dakwah Council include capacity building, community-based mentoring, culturally grounded religious approaches, development of structured dakwah materials, and collaboration with government and educational institutions. Further analysis highlights the need for policy integration at the district level, strengthening religious literacy, utilizing local wisdom, and optimizing digital media as tools for dakwah and conflict resolution.